A community assessment model appropriate for the Iranian community. - Kourosh Holakouie Naieni; Alireza Ahmadvand; Elham Ahmadnezhad; Ali Alami (Tehran University of Medical Sciences, 2014)
Community assessment is one of the core competencies for public health professionals; mainly because it gives them a better understanding of the strengths and drawbacks of their jurisdictions. We planned to recognize an appropriate model that provides a conceptual framework for the Iranian community.This study was conducted in Tehran, during 2009-2010 and consisted of two parts: a review of the literature and qualitative interview with selected experts as well as focus group discussion with health field staff. These steps were done to develop a conceptual framework: planning for a steering committee, forming a working committee, re-viewing community assessment models and projects, preparing the proposed model draft, in-depth interview and focused group discussions with national experts, finalizing the draft, and preparing the final model.Three different models published and applied routinely in different contexts. The 2008 North Carolina Community Assessment model was used as a reference. Ten national and 18 international projects were compared to the reference and one and six projects were completely compatible with this model, respectively.Our final proposed model takes communities through eight steps to complete a collaborative community assessment: form a community assessment team, solicit community participation and gain inter-sectoral collaboration, establish a working committee, empower the community, collect and analyze community's primary and secondary statistics, solicit community input to select health priorities, evaluate the community assessment and develop the community assessment document, an develop the community action plans.